New species of the wasp-mimic Parahephaestion Melzer, 1930 (Coleoptera: Cerambycidae), from Minas Gerais, Brazil, with new records - Ferreira, Gabriel S.; Corrêa, Caio C. D.; Monné, Miguel A.; Monné, Marcela L. (Zootaxa, 2024)
A new species, Parahephaestion mimicus sp. nov., is described. Two species are newly recorded for the Brazilian state of Minas Gerais: Sphalloeme costipennis Melzer, 1928 (Cerambycinae, Oemini) and Oreodera omissa Melzer, 1932 (Lamiinae, Acrocinini). Six species are new records for the RPPN Sanctuary of Caraça, (Brazil, Minas Gerais): Thalusia atrata (Melzer, 1918) (Cerambycinae, Rhopalophorini), Trachelissa pustulata (Audinet-Serville, 1834) (Cerambycinae, Trachyderini), Ateralphus dejeani (Lane, 1973) (Lamiinae, Acanthoderini), Phacellocera plumicornis (Klug, 1825) (Lamiinae, Anisocerini), Oncideres impluviata (Germar, 1823), and Psyllotoxus griseocinctus Thomson, 1868 (Lamiinae, Onciderini).